2017
DOI: 10.17113/ftb.55.02.17.4786
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic, Biochemical, Nutritional and Antimicrobial Characteristics of Pomegranate (Punica granatum L.) Grown in Istria

Abstract: SummaryThis study characterises the genetic variability of local pomegranate (Punica granatum L.) germplasm from the Slovenian and Croatian areas of Istria. The bioactive components and antioxidant and antimicrobial properties of ethanol and water extracts of different parts of pomegranate fruit were also determined, along with their preliminary nutritional characterisation. Twenty-six different genotypes identified with microsatellite analysis indicate the great diversity of pomegranate in Istria. The pomegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…It is known that bioactive compounds are variable in pomegranate, and generally in plant material, according to genetic factors, different collection stages, pedoclimatic conditions of the sampling sites (growing wild or cultivation), application of agricultural practices, and post-harvest handling [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that bioactive compounds are variable in pomegranate, and generally in plant material, according to genetic factors, different collection stages, pedoclimatic conditions of the sampling sites (growing wild or cultivation), application of agricultural practices, and post-harvest handling [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Later the antimicrobial activity of extracts of pomegranate peel and juice on cariogenic bacteria has been also highlighted by Gianmaria Fabrizio Ferrazzano (Ferrazzano et al, 2017). Moreover MiklavčičVišnjevec et al, (2017) have reported the ethanol and water extracts of pomegranate exocarp and mesocarp showed the greatest antimicrobial activity against many bacterial strains tested.…”
Section: Introductionmentioning
confidence: 90%
“…The HPLC system included a binary pump (model G7112B), Agilent 1260 Autosampler (model G7129A) and a Poroshell 120, EC-C18, 2.1 × 150 mm, 2.7 µm column (693775-902, Agilent Technologies, Santa Clara, CA, USA). The following method for the HPLC-MS analysis rests on our previous studies of phenolic compounds investigation [ 41 , 42 ]. Separation was obtained with a linear gradient of (A) water + 0.1% formic acid ( v / v ) and (B) acetonitrile/methanol (50:50, v / v ), starting at 3.0 % B and increased to 100.0% B in 15 min and held for 5 min (flow rate 0.30 mL/min, column temperature 50 °C, injection volume 1 µL).…”
Section: Methodsmentioning
confidence: 99%